Pengaruh Partisipasi Anggaran dan Sistem Akuntansi Keuangan Terhadap Kinerja Sektor Publik Dengan Variabel Moderasi - Hesti Mei Kitna; Primastiwi, Anita; Kusuma Wardani, Dewi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
The purpose of this paper is to determine the effect of budgetary participation and financial accounting systems on public sector performance with organizational culture as a moderating variable. The sample selection in this study uses a purposive sampling method. Data testing methods used are multiple regression test and absolute difference values. The result of the study indicate that budgetary participation and financial accounting systems have a significant effect on public sector performance, and organizational culture is not able to moderate the effect of budetary participation and financial accounting systems on public sector performance. Keyword: budgetary participation, financial accounting systems, public sector performance, organizational culture.